Pain Management in Mesothelioma - MacLeod, Nicholas; Klepstad, Pal; Fallon, Marie; Laird, Barry (Reports of Radiotherapy and Oncology, 2015)
Pain is the most common symptom in malignant pleural mesothelioma and can be challenging to manage. This article discusses the pathophysiology of pain in mesothelioma and provides a case history to outline management options including medication, radiotherapy, chemotherapy and cordotomy.